Biomaterials in Bearing Surface for Total Hip Arthroplasty: State of the Art - Aprato, Alessandro; Governale, Giorgio; Stucchi, Alessandro; Deregibus, Martino; Masse, Alessandro (Recent Patents on Biomedical Engineering (Discontinued), 2010)
In a recent paper published on Lancet, Learmonth defined total hip arthroplasty (THA) “the operation of the century” [1]. Since the first prostheses in 1960s, advances in bioengineering technology have driven development of hip arthroplasty; in fact better materials and designs have increased the range of motion with enhanced stability and very low wear. With these technologies today, hip arthroplasty is safe and effective not only in old patients with an important limitation of life quality but also in younger patients with high demanding activities. The purpose of this patent review is to discuss the recent technologic advances in bearing surfaces and offer an insight into the potential benefits and concerns with the alternative bearing surfaces.
Keywords: polyethylene